Pertumbuhan Cladocera jenis Chydoridae pada media kultur yang berbeda - Sambode, Denovis; Pangkey, Henneke; Lantu, Sartje (e-Journal BUDIDAYA PERAIRAN, 2013)
The aim of this study was to find out the effect of different organic fertilizers on the population growth of Chydorus sp. This research was conducted at Laboratorium of Nutrition and Food Technology, Faculty of Fishery and Marine Sciences, Sam Ratulangi University, from December, 2012 to January, 2013. The experiment was run in the Completely Randomized Design with 3 treatments and 3 replication. Chydorus sp. was cultured in 9 glass jars with a volume of 1 L each. Three treatments applied in this research included A: medium culture composed of 500ml of water and 50 grams of soil; B: medium culture composed of 500ml of water, 50 grams of soil and 10g of cow dung; C: medium culture composed of 500ml of water, 50 grams of soil and 10g of horse dung. The density of Cydorus sp. in each media was 10 individuals /500 ml water. Observation on the population growth, development of live preys, and water quality parameters was conducted for 20 days period. Data were statistically analized with Analysis of variance. The results showed the highest density of Chydorus sp. was reached by Chydorus cultured in medium with horse manure (2169 individual/500 ml), followed by medium culture with cow manure (1715 individual/500 ml), and the lowest in medium culture with soil which was 1065,33 individual/500 ml. However, Analysis of variances showed that Chydorus population growth were not significantly affected by different culture medium. Keywords: manure, liquid fertilizer, growth, Chydorus sp.